Full currency convertibility in Eastern Europe? - Bernhard Fischer; Helmut Reisen (Intereconomics, 1992)
In the countries of Eastern Europe the question as to the degree of currency convertibility is among the most important decisions to be taken when setting the framework for a free market economy. This article attempts to indicate the monetary and fiscal measures that will be required if the reform countries willing and able to be integrated into the EC and OECD are to proceed rapidly to the liberalisation of capital transactions.
Keywords: 330; System Transformation